Coherencia de Políticas para el Desarrollo en la Unión Europea - Chicharro, A. (Revista Iberoamericana de Estudios de Desarrollo)
The European policy of development cooperation falls within the framework of the principles and objectives of the external action of the Union, without shifting the responsibility of Member States in this area, but the Union and Member States cooperation policies for the development that complement and reinforce each other. Thus, the EU not only faces the challenge of Policy Coherence for Development in the horizontal plane, when their decisions concerning other jurisdictional areas that may affect partner countries, but also in the vertical plane, when it comes to coordinating their work with Member States and international organizations. Being solidarity one of the values on which the European Union is founded, the European regional framework becomes the most suitable level to increase the effectiveness of European aid, assuming responsibility for coordination and management of policy coherence.